The Effect Of Brand Authenticity On Brand Loyalty To Wardah Moisturizer, Mediated By Brand Love In Bandung City - Deby Ayu Pratydina; Efi Fitriani (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of Brand Authenticity on Brand Loyalty with Brand Love as a mediating variable on Wardah Moisturizer in Bandung City. This study uses a quantitative approach with descriptive and verification methods. Data were obtained from 120 respondents who are Wardah Moisturizer users, with data collection techniques through questionnaires. Data analysis was carried out using Partial Least Square - Structural Equation Modeling (PLS-SEM) to test the direct and indirect effects between variables. The results show that Brand Authenticity has a positive and significant effect on Brand Love, and Brand Love has a positive and significant effect on Brand Loyalty. In addition, Brand Love is proven to mediate the influence between Brand Authenticity and Brand Loyalty.